A tale of two cities by Charles Dickens - Dickens,Charles; Roddy Doyle (London: Penguin Books, 2023)
After eighteen years in the Bastille prison, Dr Manette finally leaves France and goes to live with his daughter, Lucie, in England. There, two very different men fall in love with Lucie. Lucie finds happiness, but in France a storm is coming. Soon, Lucie and her family must face the French Revolution, and one man must give Lucie everything he has.
Keywords: Easy to read; English Literature